Critérios de decisão entre hipóteses rivais nas teorias historicistas da racionalidade científica - Magro, Tamires Dal (2014)
The publication of Thomas Kuhn s The structure of scientific revolutions is considered a watershed in the philosophy of science for having presented scientific knowledge as produced by a dynamic and historically situated process. Many of the concepts introduced by the author sparked controversy in the initial reception of this work. We highlight in this dissertation Kuhn s theses on scientific revolutions, incommensurability, and scientific choice between rival hypothesis, which were interpreted by authors such as Popper, Lakatos, Laudan and Putnam as introducing elements of irrationality and relativism into Kuhn s analysis of scientific practice. In the first paper of this dissertation, we investigate passages from Structure that led to those interpretations, and track down Kuhn s later reformulations of the three controversial theses, which attempted to avoid or respond the criticisms of irrationality and relativism. We highlight the linguistic emphasis given by Kuhn in his later works to the concepts of incommensurability and scientific revolution, and show that his thesis about scientific choices remained nearly unchanged. We claim that in Kuhn s later works his theses became more precisely formulated and narrower in scope, and that they manifest a realist inclination by the author. The second paper of this dissertation develops in more detail the issue of the rationality of scientific choice. It presents briefly three theories of scientific rationality due to Kuhn, Lakatos and Laudan, and then shows some of the problems that Lakatos and Laudan s theories face due to focusing their notion of rationality on univocal rules of choice. We then indicate that there are advantages in understanding as Kuhn did the notion of rationality in terms of values that influence objectively the choices to be made without determining them univocally.